Environmental risk factors are associated with autoimmune hepatitis. (28th May 2021) - Lammert, Craig; Chalasani, Sai N.; Atkinson, Elizabeth J.; McCauley, Bryan M.; Lazaridis, Konstantinos N.
Abstract: Background: Failure of immunologic homeostasis and resultant hepatocyte destruction in autoimmune hepatitis (AIH) is likely the result of environmental triggers within a permissive genetic architecture. Aims: We aimed to identify risk factors associated with AIH in a well‐phenotyped AIH cohort. Methods: We prospectively collected environmental questionnaires from 358 AIH cases and 563 healthy controls. Response frequencies were compared using logistic regression, adjusting for age at recruitment, sex and education. Results: AIH cases were more likely to ever have a urinary tract infection (UTI) (53.6% vs 33.9%, P < .001) and recurrent UTI (more than 1 per year) (23.5% vs 15.9%, P = .002) compared to controls. Female cases more frequently had ever used oral contraceptives (83.0% vs 73.7%, P = .006), fewer pregnancies (median = 1 vs 3, P < .001) and less often used hormone replacement therapy compared to controls (28.5% vs 60.1%, P < .001). Current smoking was more prevalent in cases (18.9% vs 7.4%, P = .022), yet no difference according to historical smoking behaviours was observed. Finally, cases were less likely to have history of mumps (32.4% vs 53.1%, P = .011) and rheumatic fever (1.1% vs 4.4%, P = .028), but reported higher vaccination frequency to chicken pox (38% vs 28.1%), measles (66.5% vs 39.3%), mumps (58.7% vs 34.6%), rubella (55.3% vs 32.7%), pertussis (59.8% vs 40.1%) and pneumococcus (47.2% VS 39.4%) ( P < .002). Conclusions: Environmental factors are important in AIH pathogenesis. Replication of these findings and prospective examination may provide new insight into AIH onset and outcomes.